KORELASI DEBT TO EQUITY RATIO, CURRENT RATIO, TOTAL ASSET TURN OVER DAN NET PROFIT MARGIN DENGAN EARNING PER SHARE PADA PERUSAHAAN OTOMOTIF DI BURSA EFEK INDONESIA - Sjafii, H.; Akbar, dan Fajar Syaiful (Journal of Accounting and Strategic Finance, 2009)
This research use  free Variable The Variable is Debt To Equity Ratio,  Current Ratio, Total Asset of Turn Over and of Net Profit Margi  and also as Variable tied of that is Earning Per Share (Eps). Population which used in this research is company of Otomotif which enlist at PT. Effect Exchange Indonesia counted 7 company. Method which used in this research is correlation method of Rank Spearman used to analyse influence or relation when its data is formed by ordinal. Pursuant to result of research which have can be taken by conclusion that Debt Equity Ratio to correlate by signifikan to EPS, Current Ratio correlate by signifikan to EPS, Total Asset of Turn Over do not correlate by signifikan to EPS Net Profit Margin and [do] not correlate by signifikan to EPS.   Keywords : Debt To Equity Ratio, Current Ratio, Total Asset Turn Over, Net Profit Margin, Earning Per Share